Analisis Antrian Pada Teller : Study Kasus Pada Bank Rakyat Indonesia ( BRI ) Bogor - Sujana, Sujana (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2001)
BRI unit Bogor is a state bank moving in banking retail business . The tendency of queue by customers particularly post banking-liquidation in Indonesia has caused BRI facing the problem of tellers service. Based on the statistical process control (SPC) there were mistakes caused by human error instead by machine. These mistake were due to the service that was out of the statistical control that resulted in the service time varieties especially on peak days or at the and of every week activities